القدرة على اتخاذ القرار الدراسي لدى تلاميذ السنة الرابعة متوسط - عمامرة, سميرة; الحاج أحمد, مليكة (جامعة الوادي - University of Eloued, 2022)
تهدف الدراسة الحالية إلى الكشف عن مستوى القدرة على اتخاذ القرار الدراسي لدى تلاميذ السنة الرابعة متوسط، إلى جانب التعرف على الفروق في مستوى القدرة على اتخاذ القرار الدراسي تبعا لمتغير الجنس وإعادة السنة، ولهذا الغرض تم الاعتماد على المنهج الوصفي بأسلوبيه الاستكشافي والمقارن، حيث تم إجراء الدراسة على عينة مقدرة بـــ 160 تلميذ وتلمذة تم اختيارهم بأسلوب العينة العشوائية البسيطة، حيث طبق عليها مقياس القدرة على اتخاذ القرار المهني لــ"البلوشي"(2009). توصلت الدراسة إلى أنه يوجد مستوى منخفض في القدرة على اتخاذ القرار الدراسي لدى تلاميذ سنة رابعة متوسط، كما لا توجد فروق ذات دلالة إحصائية في مستوى القدرة على اتخاذ القرار الدراسي لدى تلاميذ سنة رابعة متوسط تعزى لمتغير الجنس، بالإضافة إلى عدم وجود فروق ذات دلالة إحصائية في مستوى القدرة على اتخاذ القرار الدراسي لدى تلاميذ سنة رابعة متوسط تعزى لمتغير إعادة السنة. Abstract: The present study aims to reveal the level of academic decision-making ability among fourth-year pupils, in addition to identifying differences in the level of academic decision-making ability according to the gender and repetition of the year variables, and for this purpose the study was based on the descriptive approach with its exploratory and comparative methods. The study was conducted on a sample of 160 male and female pupils who were chosen by the simple random sampling method. Ability to make a professional decision scale of "Al Baloushi" (2009) was used; The study found that there is a low level in the ability of academic decision-making among fourth-year pupils, and there are no statistically significant differences in the level of academic decision-making ability of fourth-year pupils due to gender, in addition to the absence of statistically significant differences in the level of academic decision-making ability of fourthyear pupils, due to the repetition of the year.
مقال
Keywords: القدرة على اتخاذ القرار الدراسي; ability of academic decision-making